The PB2 I714S mutation influenced mammalian adaptation of the H3N2 canine influenza virus by interfering with nuclear import efficiency and RNP complex assembly - Xueyun Li; Tingting Jia; Kele Wang; Liangliang Wang; Lijuan Zhou; Mao Li; Wenfei Zhu; Yuelong Shu; Yongkun Chen (Emerging Microbes and Infections)
Avian influenza viruses (AIVs) are the origin of multiple mammal influenza viruses. The genetic determinants of AIVs adapted to humans have been widely elucidated, however, the molecular mechanism of cross-species transmission and adaptation of AIVs to canines are still poorly understood. In this study, two H3N2 influenza viruses isolated from a live poultry market (A/environment/Guangxi/13431/2018, GX13431) and a swab sample from a canine (A/canine/Guangdong/0601/2019, GD0601) were used to investigate the possible molecular basis that determined H3N2 AIV adapting to canine. We found that GD0601 exhibited more robust polymerase activity in cells and higher pathogenicity in mice compared with its evolution ancestor H3N2 AIV GX13431. A series of reassortments of the ribonucleoprotein (RNP) complex showed that the PB2 subunit was the crucial factor that conferred high polymerase activity of GD0601, and the substitution of I714S in the PB2 subunit of GD0601 attenuated the replication and pathogenicity in mammal cells and the mouse model. Mechanistically, the reverse mutation of I714S in the PB2 polymerase subunit which was identified in AIV GX13431 reduced the nuclear import efficiency of PB2 protein and interfered with the interactions of PB2-PA/NP that affected the assembly of the viral RNP complex. Our study reveals amino acid mutation at the position of 714 in the nuclear localization signal (NLS) area in PB2 plays an important role in overcoming the barrier from poultry to mammals of the H3N2 canine influenza virus and provides clues for further study of mammalian adaptation mechanism of AIVs.